2003
DOI: 10.1001/archpsyc.60.6.553
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Efficacy of Second-Generation Antipsychotics

Abstract: Some SGAs are more efficacious than FGAs, and, therefore, SGAs are not a homogeneous group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
500
3
33

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 911 publications
(567 citation statements)
references
References 150 publications
31
500
3
33
Order By: Relevance
“…The equivalence of olanzapine and amisulpride with regard to positive and negative symptoms has also been demonstrated in another randomized comparison study with 377 acutely psychotic schizophrenic patients, where 2 months after treatment onset no differences in BPRS total or BPRS factor scores, or depressive symptoms (Martin et al, 2002) were evident. A meta-analysis by Davis et al (2003) indicated that olanzapine and amisulpride are both equally superior to conventional antipsychotics regarding PANSS or BPRS total scores (effect sizes, olanzapine,…”
Section: Discussionmentioning
confidence: 99%
“…The equivalence of olanzapine and amisulpride with regard to positive and negative symptoms has also been demonstrated in another randomized comparison study with 377 acutely psychotic schizophrenic patients, where 2 months after treatment onset no differences in BPRS total or BPRS factor scores, or depressive symptoms (Martin et al, 2002) were evident. A meta-analysis by Davis et al (2003) indicated that olanzapine and amisulpride are both equally superior to conventional antipsychotics regarding PANSS or BPRS total scores (effect sizes, olanzapine,…”
Section: Discussionmentioning
confidence: 99%
“…Roughly speaking, clozapine has been found to be almost 0.5 effect size units better than FGAs; and olanzapine, risperidone, and amisulpride about 0.25 effect size units better than FGAs (Davis et al, 2003). For these empirical results to be completely explained by such an artifact, the bias would need to produce approximately a 0.5 effect size unit (which corresponds essentially to a 12-point PANSS total score) difference of SGA vs FGA to explain clozapine's greater efficacy (or one-half that to explain the difference of olanzapine or risperidone vs an FGA (Davis and Chen, 2002)).…”
Section: Interpretation Of Meta-analysis Size Effectsmentioning
confidence: 99%
“…We used a previously published dataset from our metaanalysis of SGAs vs FGAs of 124 RCTs and the methodology has been previously reported in detail (Davis et al, 2003). Our primary outcome was improvement as measured with the Positive and Negative Syndrome Scale (PANSS; Kay et al, 1987).…”
Section: Source Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…At a population level several studies have reported an association between increasing antidepressant use and a reduction in suicide rates, though the potential effect of confounders makes it impossible to prove that this is a causal relationship (Henriksson and Isacsson, 2006;Olfson et al, 2003). Antipsychotic drugs have proven efficacy in the acute (Davis et al, 2003) and long-term treatment of schizophrenia (Leucht et al, 2003b) and the treatment of mania (Perlis et al, 2006). There is increasing evidence that specific atypical antipsychotics may have benefit in other phases of bipolar illness Tohen et al, 2005).…”
Section: Avoiding Adverse Effectsmentioning
confidence: 99%